DEVELOPMENT OF A TRAINING MODEL TO IMPROVE SCIENCE TEACHERS’ COMPETENCE IN DESIGNING SCIENCE LITERACY ASSESSMENTS FOR JUNIOR HIGH SCHOOLS - Triwahyuni, Nugrahety; Prasetyorini, Prasetyorini; Rubini, Bibin (Universitas Pakuan, 2025)
Scientific literacy is a fundamental skill needed to prepare students for 21st-century demands. Despite its importance, Indonesia’s 2022 PISA results indicate that students’ scientific literacy remains below the international standard, mainly due to teachers’ limited ability to design literacy-based assessments. This study aims to develop and evaluate the effectiveness of the Blended Learning for Assessment and Scientific Literacy (BLAST-SCI) model, integrated with a Professional Learning Community (PLC), in improving junior high school science teachers’ competence in developing scientific literacy assessments. Using a Research and Development (RD) approach adapted from the ADDIE framework, the study involved 30 science teachers from Bogor City. Data were collected through observation, interviews, questionnaires, and document analysis, which is analyzed using paired t-tests, N-Gain, ANOVA, and Aiken’s V. The findings show that the PLC-integrated BLAST-SCI model significantly improved teachers’ competence, as indicated by meaningful pretest–posttest differences (p 0.05), high N-Gain scores (73–84%), and increased instrument validity (Aiken’s V = 0.817). Participants gave positive responses to the model’s materials, facilitation, and relevance. In conclusion, the PLC-integrated BLAST-SCI model is valid, effective, and practical for professional development, contributing to the enhancement of teachers’ assessment literacy and promoting students’ scientific literacy through contextual and high-quality assessments.